(untitled) (International Journal of Engineering and Computer Science, 2013)
This paper describes a Model Reference Adaptive System (MRAS) for speed control of the Induction Motor drive (IM) without a speed sensor. In this scheme an Adaptive Pseudoreduced-order Flux Observer (APFO) is used instead of the Adaptive Full-order Flux Observer (AFFO), an APFO is used for estimate the IM rotor speed and stator resistance, and these are used as feedback signals for the Field Oriented Control (FOC), which is a widely used control method for Induction Motor drive (IM). Simulation results show that the proposed scheme can estimate the motor speed under various adaptive PI gains and estimated speed can replace to measured speed in sensorless induction motor drives, this scheme is more efficient at very low speed, and also observed line currents, torque and speed under no-load and load conditions.